Anti-rolling analysis and resistance optimization of a new anti-rolling hydrofoil for the trimaran vessel. (15th March 2023) - Zhang, Yihan; Hu, Jingfeng; Ma, Shan; Wang, Ping
Abstract: The roll motion performance of the trimaran vessel is not as good as expected at low forward speed in high sea conditions. A new designed anti-rolling hydrofoil is proposed, which connects the main hull and the side hull below the waterline to provide the reverse roll moment by the huge hydrodynamic pressure during the roll motion. The anti-rolling effect of four creative schemes of the hydrofoils are analyzed by a set of high-precision numerical calculation method combined with CFD and 3D potential flow theory for roll damping and roll motion in waves. The roll damping characteristics and the mechanism of the hydrofoil are analyzed in detail combined with flow field analysis. The results indicate the high anti-rolling efficiency for the trimaran vessel. In order to make this device close to the engineering application, the profile and angle of attack are optimized to reduce the resistance. Finally, the anti-rolling hydrofoil with a good comprehensive performance is obtained, providing a valuable reference for the seakeeping design of the trimaran vessel. Highlights: A new creative anti-rolling hydrofoil for trimaran vessel with remarkable anti-rolling effect in average of about 25% at zero speed and that of 35% at high forward speed. Anti-rolling effect and detailed mechanism analysis of anti-rolling hydrofoil. An optimized anti-rolling hydrofoil with no resistance adding is obtained by optimization of profile and attack angle by CFD method.